A rare cause of intercostal neuralgia: Ancient schwannoma of the chest wall - (:unkn) unknown (MARMARA UNIV, FAC MEDICINE, 2017)
Intercostal neuralgia is a rare condition that causes pain along the intercostal nerves. Neural tumors of the chest mostly arise from mediastinum and only less than 5-10% of primary tumors originate from intercostal nerves. These patients are usually asymptomatic. Herein, we report a 42-year-old male patient with severe intercostal neuralgia due to the schwannoma of the chest wall. The patient underwent surgical resection and his histopathological diagnosis was a very rare type of schwannoma: ancient schwannoma. Resecting the tumor relieved his pain.
Keywords: Ancient schwannoma; Schwannoma; Schwannoma of the chest wall; TUMORS